PENGARUH DOSIS PUPUK KANDANG SAPI TERHADAP PERTUMBUHAN DAN HASIL TANAMAN TERUNG UNGU DAN TERUNG HIJAU (Solanum melongena L .) - Doni Sriyanto, Puji Astuti, dan Akas Pinaringan Sujalu (Universitas 17 Agustus 1945 Samarinda, 2015)
The purpose of this study was to determine the effect of the application of cow manure and egg plant varieties, and their interactions, as well as to find proper dosage of cow dung and a variety for better growth and production. The study was conducted from February to June 2013, in the village of New Melapeh Linggang Bigung Subdistrict, West Kutai. The randomized design was employed for this study with a factorial 2 x 4 and 3 replications. The first factor is the eggplant variety (V) which consists of two sub-factors: V1 (v1) and V2 (v2). And the second factor is the dose of cow manure (P), consists of four sub-factors: 0 tonnes/ha (p0), 5 tons/ha, equivalent to a 2:42 g/plot (p1), 10 tons/ha, equivalent to 4.85 g/plot (p2), and 15 tons/ha, equivalent to 7.62 g/plot (p3).The results showed that the best variety is V1, and the dose of cow manure affected significantly on the length of the plant at 15, 30, and 45 days after planting, the number of fruits per plant, fruit weight per plant, fruit diameter, affected significantly on the length of the fruit , but it does not affect significantly on the weight of fruit per plant. The best production obtained by treatment of 15 tons/ha with a 7.26 g, and the least one is 5 tons/ha with a 2.42 g.Meanwhile, the interaction between the dose of cow manure and egg plan varieties affected very significantly on the length of the plant at 15 and 30 days after planting, affected significantlyon the number of fruits per plant and fruit length, but it does not affect significantly on the length of the plant in 45 days after planting, fruit weight per plant and fruit diameter.